ANALISIS PENGARUH KEBIJAKAN DEVIDEN DAN KINERJA KEUANGAN TERHADAP HARGA SAHAM (Studi Empiris Perusahaan Sektor Industri Dasar Dan Kimia Di BEI Tahun 2018-2022) - Feby Annisa Dewi; Sunarto Sunarto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to analyze the influence of dividend policies and financial performance on stock prices in the basic and chemical industry sector companies listed on the Indonesia Stock Exchange (IDX) from 2018-2022. A quantitative method was employed by collecting secondary data from the companies' financial statements and annual reports. The analysis was conducted through descriptive statistical tests, normality tests using skewness and kurtosis, and classic assumption tests such as multicollinearity, heteroskedasticity, and autocorrelation tests. The results of multiple regression analysis indicate that the Current Ratio (CR) has the most dominant influence on stock prices, followed by Debt to Equity Ratio (DER) and Activity, with a significant positive effect. In contrast, Return on Assets (ROA) and Dividend Payout Ratio (DPR) do not significantly affect stock prices. Specifically, liquidity levels (CR) play the strongest role, indicating the crucial role of company liquidity in influencing stock prices. Keywords: Dividend Policy, Financial Performances, Stock Price.